Ex vivo DNA Assembly - Fisher, Adam B.; Canfield, Zachary B.; Hayward, Laura C.; Fong, Stephen; McArthur, George H. (Frontiers in Bioengineering and Biotechnology, 2013)
Even with decreasing DNA synthesis costs there remains a need for inexpensive, rapid and reliable methods for assembling synthetic DNA into larger constructs or combinatorial libraries. Advances in cloning techniques have resulted in powerful in vitro and in vivo assembly of DNA. However, monetary and time costs have limited these approaches. Here, we report an ex vivo DNA assembly method that uses cellular lysates derived from a commonly used laboratory strain of Escherichia coli for joining double-stranded DNA with short end homologies embedded within inexpensive primers. This method concurrently shortens the time and decreases costs associated with current DNA assembly methods.